Utilization of Plant in the Panggih Temanten Traditional Rituals in Ogan Komering Regency Ulu Timur South Sumatera - Ulmillah, Aulia; Saputri, Dwijowati Asih; Kamelia, Marlina; Baika, Febta Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
One of the sub-districts in the East Ogan Komering Ulu (OKU) district of South Sumatra, namely Buay Madang Timur, the people are migrants (transmigrants), especially from the Javanese tribe and still preserve the traditional ritual of the Panggih Temanten marriage. The aim of the study was to determine the various kinds of plant families used in the traditional rituals of Panggih Temanten Javanese people in Buay Madang District, East OKU Regency, South Sumatra. This research is a qualitative type with sampling using purposive sampling and snowball sampling. Data collection through structured interviews to selected respondents. The results showed that there were 13 families consist of Arecaceae, Musaceae, Asparagaceae, Euphorbiaceae, Moraceae, Rosaceae, Annonaceae, Nyitaginaceae, Rubiaceae, Asteraceae, Magnoliaceae, Piperaceae, and Oleaceae. The plant patrs used include stem, flower and leaf